ANALISA PELAYANAN JAMAAH HAJI DAN UMRAH DALAM MEMBANGUN CITRA POSITIF PADA PT. RIYADHULJANNAH TOUR DAN TRAVEL KABUPATEN PANDEGLANG - Atiah, Umu; Fatari, Fatari; Hartoko, Gatot (Jurnal Valuasi: Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2024)
This research aims to find out the strategies used by customer service in serving Hajj and Umrah pilgrims and what efforts are made by the company to gain a positive image among the community.To identify these problems in depth, this research uses a descriptive method with a qualitative approach. Data collection techniques use interviews, observation and documentation. Data analysis carried out by researchers is data reduction, data presentation, and finally decision making. The findings from this research state that this service strategy for Umrah and Hajj pilgrims plays a very important role in building a positive image in the eyes of the public for the company itself. From this research, it is concluded that the strategy analysis in serving Hajj and Umrah pilgrims is to consistently implement the principles of service quality, create attractive promotions, collaborate with other companies, improve the work structure again. And analysis of strategies for building a positive image in the eyes of the public by making honest product promotions, establishing good relationships with the congregation, creating congregational alumni associations